Mitochondrial ATP synthesis is essential for efficient gametogenesis in Plasmodium falciparum - Penny C. Sparkes; Mufuliat Toyin Famodimu; Eduardo Alves; Eric Springer; Jude Przyborski; Michael J. Delves (Communications Biology)
Abstract Plasmodium male and female gametocytes are the gatekeepers of human-to-mosquito transmission, therefore essential for propagation of malaria within a population. Whilst dormant in humans, their divergent roles during transmission become apparent soon after mosquito feeding with a rapid transformation into gametes – males forming eight motile sperm-like cells aiming to fertilise a single female gamete. Little is known about how the parasite fuels this abrupt change, and the potential role played by their large and elaborate cristate mitochondrion. Using a sex-specific antibody and functional mitochondrial labelling, we show that the male gametocyte mitochondrion is less active than that of female gametocytes and more sensitive to antimalarials targeting mitochondrial energy metabolism. Rather than a vestigial organelle discarded during male gametogenesis, we demonstrate that mitochondrial ATP synthesis is essential for its completion. Additionally, using a genetically encoded ratiometric ATP sensor, we show that gametocytes can maintain cytoplasmic ATP homeostasis in the absence of mitochondrial respiration, indicating the essentiality of the gametocyte mitochondrion for transmission alone. Together, this reveals how gametocytes responsively balance the conflicting demands of a dormant and active lifestyle, highlighting the mitochondria as a rich source of transmission-blocking targets for future drug development.